Diaphragmatic ultrasound: Prospects as a tool to assess respiratory muscle involvement in amyotrophic lateral sclerosis. Issue 1 (5th October 2021) - Rajula, Rahul Reddy; Saini, Jitender; Unnikrishnan, Gopikrishnan; Vengalil, Seena; Nashi, Saraswati; Bardhan, Mainak; Huddar, Akshata; Chawla, Tanushree; Sindhu, Dodmalur Mallikarjuna; Ganaraja, Valakunja Harikrishna; Polavarapu, Kiran; Preethish‐Kumar, Veeramani; et al.
Abstract: Background: Ultrasonography (USG) of the diaphragm is a promising alternative to pulmonary function tests (PFT) for assessing respiratory function in amyotrophic lateral sclerosis/motor neuron disease (ALS/MND). Methods: We studied 33 patients fulfilling Awaji criteria (definite = 14; probable = 12; possible = 7) and 33 age and gender‐matched controls. Diaphragm thickness was measured using USG at the end of expiration (DTex) and end of inspiration (DTin). The thickness ratio (TR) was calculated as DTin/DTex. The mean age at onset and duration were 49.73 ± 12.7 years and 13.57 ± 9.7 months, respectively. Men = 25 (75.8%); Limb onset ALS/MND = 24 patients (72.7%); bulbar onset = 9 (27.3%). Results: Compared to controls, ALS/MND patients had reduced mean DTex (2.22 ± 0.29 mm vs. 2.02 ± 0.32 mm, p = .012) and DTin (4.0 ± 0.71 mm vs. 3.41 ± 0.38 mm, p < .001). PFTs done in 31 patients showed restrictive abnormality in 80.6%. Significant positive correlation was seen between percentage of predicted forced vital capacity (FVC%) and DTin ( p = .009) and TR ( p = .037) but not with DTex ( p = .852). No significant correlation was seen between diaphragmatic thickness and other PFT parameters or ALSFRS scores. Conclusion: The diaphragmatic thickness showed a significant decrease in ALS/MND as compared to controls. End‐inspiratory diaphragmatic thickness and TR correlated well with %FVC. Thus, diaphragmatic USG could be a potential alternative to PFTs in assessing respiratory function in ALS/MND patients having the advantage of less patient participation and ease of performing in late stages of ALS/MND. Abstract : Measurement of diaphragmatic thickness on ultrasound. (A) Diaphragm thickness measurement in end of expiration. (B) Diaphragm thickness measurement in end of inspiration